Perspectives of low-income mothers about their intimate partner relationships. Issue 5 (20th October 2021) - Aguiniga, Donna M.; Trawver, Kathi R.
ABSTRACT: To help fill the gaps in their support system and meet the needs of their families, low income mothers may develop or maintain intimate partner relationships (IPRs). This study employs the voices of 22 low-income mothers to examine the factors that influence how low-income mothers' perceive their intimate partner relationships. Researchers employed a semi-structured interview guide to encourage participants' reflection about characteristics they seek in an intimate partner, their most recent relationships, and the types of help they want from an intimate partner. A grounded theory approach was used to identify key themes. Identified themes include the impact of participants' personal history and the centrality of their role as mother. Past experiences of abuse and violence experienced by many low-income mothers made it difficult for them to trust. This research provides insight into the experiences of low-income mothers and IPRs that can be used in future theoretical model development. Practice implications include the need for trauma-informed services and increased social service programs for mothers leaving problematic relationships.